MatPLC : the truly open automation controller - Mário Jorge Rodrigues de Sousa (2002)
The MatPLC is an international project to create and distribute a program similar to a PLC (Programmable Logic Controller) for POSIX Operating Systems, and licensed under the GNU Public License. Considerable effort has been put into designing a robust and scalable system, which includes novel features and capabilities not found in standard PLCs.